Emerging Technology Trends in Power Electronics, Communication for Water Supply Management for Public Drinking (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In Today's Scenario there is a rapid increasing of population development and development of urban residential area, but as compare with rapid increasing of consumers still the water distribution system is using traditional method, which are still not atomized. Sideways with this alternative problem in the water supply system are facing now a days that public crowd are using suction pumps to suck the water directly from the domestic street pipeline. To overcome from this problem, the best resolution is to improve the automation and monitoring architectures which contain a management and control system for the real time installation, PLC (Programmable Logic Controllers) with basic occupations communication systems, standard interfaces or dedicated ones with proximity sensors, which includes all network components like flow sensor, GSM modules, pH sensor, electrical drive elements, measuring devices, etc. by using proposed solution to be improving and developing the PLC & SCADA based water monitoring and theft prevention, better water utilization and Controlling of water Distribution system with better efficiency and Cost Optimization & reduction in Operational & Maintenance. Control System is further coupled to SCADA unit. 'this paper primarily emphases mostly to a control system for controlling and monitoring within a Water Distribution System. By the using of latest Process Automation and Monitoring system based upon operation of a PLC and automation systems including all the network components represents the best way to improve the water distribution technological process. It subsidizes greatest profit and minimal consumption like water loss, consumption of electrical power, overtime work of pumps etc.